Diminishing partnership: bankers strategic response to Shariah compliant home financing - Abdul Razak, Dzuljastri; Ismail, Yusof (KENMS-IIUM Press, 2011)

(untitled)
Diminishing Partnership (DP) is a relatively new concept in home financing based on equity compared to the established debt concept used in conventional and BBA home financing. Under DP home financing, the customer and bank share profit based on the rental value of the house instead of predetermined interest rate where the bank gains profit upfront. As such DP is claimed to be fairer and more flexible than debt financing which result in more justice, equality and cater for societal well being in line with the Maqasid al Shariah (Al-Ghazali, 1937). This research adopted a mixed method by using questionnaires to survey the perceptions of customers. The perceptions of bankers and Shariah scholars were obtained by means of semi structured interviews. Four common issues were investigated namely,concept used, method of computing and pricing, Shariah compliant and preference for the product. The main findings indicated that customers perceived DP home financing meet their needs better than the debt financing concept. The Shariah scholars also agreed that DP possesses justice, fairness and cater for the well being of individual and society. Contrary to expectation, the overall views of the bankers support the implementation of DP except a few reservations regarding pricing and operations. The results imply that DP home financing concept is more widely acceptable by the three stakeholders compared to the existing BBA. The results provide a strategic response for bankers to promote DP home financing to their existing and potential customers as a Shariah compliant home financing product.